PENERAPAN PERENCANAAN PAJAK ATAS PAJAK PENGHASILAN - Wibisono, Bagus Tutuka; Budiarso, Novi Swandari (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2021)
This study aims to describe how the implementation of appropriate tax planning in order to minimize the payment of income tax. In optimizing tax planning, a strategy that can be done is to make a nominative list related to entertainment expenses, management of food facilities, health and communication for employees, the use of the gross-up method in calculating employee salaries. Tax planning resulted in tax savings of IDR 7,022,500.00. The available cash flow from the tax savings can be maximized to support other operational activities.